Association between Porphyromonas Gingivalis and systemic diseases: Focus on T cells-mediated adaptive immunity - Li, Cheng; Yu, Ran; Ding, Yumei (Frontiers in Cellular and Infection Microbiology, 2022)
The association between periodontal disease and systemic disease has become a research hotspot. Porphyromonas gingivalis (P. gingivalis), a crucial periodontal pathogen, affects the development of systemic diseases. The pathogenicity of P. gingivalis is largely linked to interference with the host’s immunity. This review aims to discover the role of P. gingivalis in the modulation of the host’s adaptive immune system through a large number of virulence factors and the manipulation of cellular immunological responses (mainly mediated by T cells). These factors may affect the cause of large numbers of systemic diseases, such as atherosclerosis, hypertension, adverse pregnancy outcomes, inflammatory bowel disease, diabetes mellitus, non-alcoholic fatty liver disease, rheumatoid arthritis, and Alzheimer’s disease. The point of view of adaptive immunity may provide a new idea for treating periodontitis and related systemic diseases.